2011
DOI: 10.1080/10454446.2011.618788
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Analysis of the Relative Importance of Service Quality for Two UK Grocery Retailers

Abstract: This article identifies the relative importance of service quality across two grocery store formats. Research to date, indicates that within the grocery sector, customers expect value for money in terms of product quality, nutritional value and service quality. If these attributes are met in relation to the customers' perceived risk, it is more likely that customer satisfaction and retention will occur. In difficult competitive, social and economic circumstances, some sources indicate that there will be a trad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…According to recent works, retail environment is changing due to increasing competition and consumers' demand with greater expectations (Ryding, 2011). Past studies showed how the current retailers' strategies towards the usage of advanced technologies in the points of sale do not satisfy totally consumers' expectations (Pantano and Viassone, 2012).…”
Section: Demand Pull Perspective For Innovating In Retailingmentioning
confidence: 97%
See 3 more Smart Citations
“…According to recent works, retail environment is changing due to increasing competition and consumers' demand with greater expectations (Ryding, 2011). Past studies showed how the current retailers' strategies towards the usage of advanced technologies in the points of sale do not satisfy totally consumers' expectations (Pantano and Viassone, 2012).…”
Section: Demand Pull Perspective For Innovating In Retailingmentioning
confidence: 97%
“…Past studies showed how the current retailers' strategies towards the usage of advanced technologies in the points of sale do not satisfy totally consumers' expectations (Pantano and Viassone, 2012). Therefore, understanding what consumers expect by designing the service that fits the expectations and delivering this service allows retailers to fulfill the gap between clients' expectations and effective perception of the service with benefits for satisfaction and loyalty (Ryding, 2011). Concerning advanced technologies in retailing, consumers mainly expect that these ones will improve their shopping activities, by providing new tools, services and functions for saving time while purchasing (Pantano and Viassone, 2012).…”
Section: Demand Pull Perspective For Innovating In Retailingmentioning
confidence: 98%
See 2 more Smart Citations